Systematic literature review: Interpretation of lah discourse particles in Malaysian speech [Sorotan literatur bersistematik: Interpretasi partikel wacana lah dalam ujaran masyarakat Malaysia] - Anida Sarudin (Tanjung Malim, 2023)
Systematic literature review: Interpretation of lah discourse particles in Malaysian speech [Sorotan literatur bersistematik: Interpretasi partikel wacana lah dalam ujaran masyarakat Malaysia] by Anida Sarudin